2008
DOI: 10.1364/ao.48.000022
|View full text |Cite
|
Sign up to set email alerts
|

More on analyzing the reflection of a laser beam by a deformed highly reflective volume Bragg grating using iteration of the beam propagation method

Abstract: A further extension of the iteration method for beam propagation calculation is presented that can be applied for volume Bragg gratings (VBGs) with extremely large grating strength. A reformulation of the beam propagation formulation is presented for analyzing the reflection of a laser beam by a deformed VBG. These methods will be shown to be very accurate and efficient. A VBG with generic z-dependent distortion has been analyzed using these methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Scattering losses are less than 1% and comparable to the residual reflectivity of the antireflection coated entrance and exit faces. The asymmetry in the side lobes of the measured curve could be due to a z-dependent background index change, or grating period distortion [9,10]. The polarization dependence of a volume holographic grating should be negligible when the angle between the incident and diffracted beams is <10° [11], and we have confirmed this experimentally.…”
Section: Experiments and Calculationssupporting
confidence: 71%
“…Scattering losses are less than 1% and comparable to the residual reflectivity of the antireflection coated entrance and exit faces. The asymmetry in the side lobes of the measured curve could be due to a z-dependent background index change, or grating period distortion [9,10]. The polarization dependence of a volume holographic grating should be negligible when the angle between the incident and diffracted beams is <10° [11], and we have confirmed this experimentally.…”
Section: Experiments and Calculationssupporting
confidence: 71%
“…Some numerical calculations on how VBGs are affected by absorption are available in the literature [18][19][20][21]. For a reflected laser beam Jelger et al [18] showed that the heat distribution loosely follows the intensity distribution in the grating for a highly reflective VBG with an absorption coefficient of 10 −3 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…For a reflected laser beam Jelger et al [18] showed that the heat distribution loosely follows the intensity distribution in the grating for a highly reflective VBG with an absorption coefficient of 10 −3 cm −1 . Shu et al [19][20][21] have developed a numerical model for the grating reflectivity for a given grating deformation due to, for instance, absorbed radiation. In [19] an example is given corresponding to the case when a nonresonant beam is heating up the grating and another similar beam is reflected.…”
Section: Introductionmentioning
confidence: 99%
“…A few examples on numerical calculations on how VBGs are affected by absorption have been reported [7,[11][12][13]. For a reflected laser beam, Jelger et al [7] showed that the heat distribution loosely follows the intensity distribution in the grating for a highly reflective VBG with an absorption coefficient of around 10 −3 cm −1 , i.e., when the absorbed power is relatively low and does not affect the intensity distribution within the grating.…”
Section: Introductionmentioning
confidence: 99%
“…For a reflected laser beam, Jelger et al [7] showed that the heat distribution loosely follows the intensity distribution in the grating for a highly reflective VBG with an absorption coefficient of around 10 −3 cm −1 , i.e., when the absorbed power is relatively low and does not affect the intensity distribution within the grating. Shu and co-workers [11][12][13] have developed a numerical model for the grating reflectivity for a given grating deformation due to, e.g., absorbed radiation. In [11], an example is given corresponding to the case when a nonresonant beam is heating up the grating and another similar beam is being reflected.…”
Section: Introductionmentioning
confidence: 99%